2020
DOI: 10.1177/1747519820958626
|View full text |Cite
|
Sign up to set email alerts
|

An efficient one-pot synthesis and biological evaluation of novel (E)-2-aroyl-4-arylidene-5-oxotetrahydrofuran derivatives

Abstract: An efficient one-pot base-mediated approach to ( E)-2-aroyl-4-arylidene-5-oxotetrahydro-furans is developed. Nine ( E)-2-aroyl-4-arylidene-5-oxotetrahydrofurans are synthesized in good yields via tandem Passerini and cyclization reactions, starting from Baylis–Hillman acids, aryl glyoxals, and isocyanides at room temperature in the presence of Cs2CO3. In addition, the MTT assay is used to evaluate their cytotoxicities toward the cervical cancer cell lines C-33A, CaSki, and SiHa and the hepatocarcinoma cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Based on tandem I-MCR/S N cyclization, we previously prepared (E)-2-aroyl-4-arylidene-5-oxopyrrolidine 27 and (E)-2-aroyl-4-arylidene-5-oxotetrahydro rhoplaladin analogs furan. 28 In the analogous way, seven Acanthus ilicifolius Linn alkaloid 2-benzoxazolinone derivatives 6 have been obtained in good to excellent yields, and the highest yield is 90%. The yields of compounds 6 were mainly related to the nature of the Ar substituent on the benzaldehyde (2), and not on the R group of the alkyl isocyanides (3).…”
Section: Resultsmentioning
confidence: 97%
“…Based on tandem I-MCR/S N cyclization, we previously prepared (E)-2-aroyl-4-arylidene-5-oxopyrrolidine 27 and (E)-2-aroyl-4-arylidene-5-oxotetrahydro rhoplaladin analogs furan. 28 In the analogous way, seven Acanthus ilicifolius Linn alkaloid 2-benzoxazolinone derivatives 6 have been obtained in good to excellent yields, and the highest yield is 90%. The yields of compounds 6 were mainly related to the nature of the Ar substituent on the benzaldehyde (2), and not on the R group of the alkyl isocyanides (3).…”
Section: Resultsmentioning
confidence: 97%
“…We have previously synthesized rhopaladins’ analog ( E )-2-aroyl-4-arylidene-5-oxopyrrolidine (RPDP serial chemicals, see Scheme 1 ) from Baylis–Hillman acid (2-bromomethyl-3- p -fluorobenzyl-2-propenoic acid), primary amines, arylglyoxal, and isocyanide via a one-pot approach which is based on Ugi condensation and intramolecular S N cyclization ( Zhu et al, 2020 ). Moreover, the rhopaladins’ analogs ( E )-2-aroyl-4-arylidene-5-oxopyrrolidine inhibited CaSki human cervicocarcinoma cell proliferation, induced cell apoptosis, and downregulated the E6/E7 mRNA expression ( Zeng et al, 2013 ; Wang et al, 2021 ). However, it has a high selectivity to cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that rhopaladins A-D alkaloids (Janosik et al, 2002;Méndez et al, 2018) (Scheme 1) present in marine cysts have significantly biological activities. We have previously synthesized several different series of rhopaladins' analogs, such as (E)-2-aroyl-4-arylidene-5-oxopyrrolidines (Scheme 1), and (2E, 4E)-2-styryl-4-arylidene-5-oxopyrrolidines, via multi-component one-pot method starting from Baylis-Hillman acid, and found that these compounds showed good anti-proliferation and apoptosis-inducing effects on cervical cancer cells and liver cancer cells, respectively (Zeng et al, 2013;Zhu et al, 2020;Wang et al, 2021;Wang et al, 2021;Kong et al, 2021;Zhu et al, 2022). Baylis Hillman (B-H) reaction is a coupling reaction between active alkenes and electrophiles under catalyst, which can be used to synthesize compounds with polyfunctional groups under mild reaction conditions (Huang and Cui, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…γ-Lactone is a common chemical skeleton in many synthetic and natural products, mainly composed of five-member lactone heterocycles, which possess many biological properties and are key intermediates in the synthesis of major antiviral and anticancer nucleoside analogs (Julien et al, 2018). Therefore, by combining Passerini reaction with Baylis Hillman reaction, γlactone derivatives of (E)-4-arylidene-5-oxotetrahydrofuran derivatives (RPDF serial chemicals, which are other analogs of rhopaladins, Scheme 1) were synthesized via a tandem Passerini 3CC/S N cyclization one pot method (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%